A NEW ORYCTOCENOSIS OF THE AQUATIC VERTEBRATE COMMUNITY FROM THE LATE PERMIAN OF CENTRAL RUSSIA - Sennikov A.G.; Gubin Yu.M.; Golubev V.K.; Bulanov V.V.; Ivakhnenko M.F.; Kurkin A.A. (My University, 2003)
In the Permian strata (Upper Tatarian Substage, Vyatkian Horizon, Scutosaurus karpinskii Tetrapod Zone, Chroniosuchus paradoxus Subzone) near the town of Gorokhovets (Vladimir Region), a locality of Late Permian vertebrates was discovered. As regards to the taxonomic composition and the abundance of specimens, this is one of the richest localities in Russia. The new oryctocenosis contains 12 tetrapod forms of the Sokolki Assemblage, including tempospondyls, anthracosaurians, seymouriamorphs, pareiasaurians, gorgonopians, therocephals, cynodonts, and dicynodonts, and at least eight fish forms. The oryctocenosis is dominated by fish and aquatic and semiaquatic tetrapods. The locality was formed in conditions with an extensive lowland with a strongly meandering system and branching channels of constant and temporary streams which alternate with vast sandy and silty banks.
Keywords: Permian; Paleozoic::Permian; Палеозой::Пермская